If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -6) + 4 = 8x + -6 Reorder the terms: 6(-6 + x) + 4 = 8x + -6 (-6 * 6 + x * 6) + 4 = 8x + -6 (-36 + 6x) + 4 = 8x + -6 Reorder the terms: -36 + 4 + 6x = 8x + -6 Combine like terms: -36 + 4 = -32 -32 + 6x = 8x + -6 Reorder the terms: -32 + 6x = -6 + 8x Solving -32 + 6x = -6 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -32 + 6x + -8x = -6 + 8x + -8x Combine like terms: 6x + -8x = -2x -32 + -2x = -6 + 8x + -8x Combine like terms: 8x + -8x = 0 -32 + -2x = -6 + 0 -32 + -2x = -6 Add '32' to each side of the equation. -32 + 32 + -2x = -6 + 32 Combine like terms: -32 + 32 = 0 0 + -2x = -6 + 32 -2x = -6 + 32 Combine like terms: -6 + 32 = 26 -2x = 26 Divide each side by '-2'. x = -13 Simplifying x = -13
| Y+X/7Y=3/7 | | -3/2v=21 | | -x+1/6-5-3x/4=31/5 | | 5/6z=15 | | 2(v-2)+2v=8 | | -3/2v+21 | | ln(x)=.75ln(16)+ln(20)-3ln(8) | | xy-2y=3x+t | | 1/10p=10-1/40p | | 18/2x=81 | | 4x-6(16)=-18 | | 3(x-1)/2 | | -4x+13+5x=3+x+10 | | -9+2n/9 | | 8x-2=6x+3 | | -7-(-43)=x/9 | | b=8/3(j-68) | | x/3=2x/15+8 | | y=3.08sqrt(75)+20.08 | | (13x-2)7=133 | | z/2+1=4-z/2 | | J+2/3+5j/6=4j-5/12 | | 58+(x-7)=180 | | 175m-75m+47500=50000-150m | | 3x/20-6x=1/10 | | -13+-13= | | -2(b-5)=-4 | | -4x+4y=-14 | | 5-x=12x-8 | | 7n+12=-6n | | 2(x-1)=3(x+4) | | 3(2x-1)-6=2x+3 |